Варьирование в языке и смежные с ним явления: монография - Александров О. А. Олег Анатольевич; Богословская З. М. Зоя Матиновна; Митяева А. П. Анна Павловна; Новикова В. С. Вера Станиславовна; Петрунина С. П. Светлана Петровна; Савилова С. Л. Светлана Леонидовна; Щеголихина Ю. В. Юлия Викторовна; Щитов А. Г. Александр Григорьевич; Щитова Д. А. Дарья Александровна; Щитова О. Г. Ольга Григорьевна; Ярица Л. И. Людмила Ивановна (Томск, Изд-во ТПУ, 2015)
Заглавие с титульного экрана